Evaluasi Program Pelatihan Kewirausahaan Untuk Menciptakan Lapangan Kerja - Safitri, Arin Nela (Jurnal Administrasi Publik, 2015)
Abstract Evaluation Of A Training Program In Entrepreneurship To Create Jobs. Businesses that the Government reduce the number of people who have not worked in the city of Surabaya is to do entrepreneurial training to people so that they can get the job done. If it does not do business that the number of unemployed will increase. With the program of this Government could be expected to open up the opportunity to work for the community. The target of this community's entrepreneurial training program. This program assisted trusted institutions in order to achieve success. With it we will know the Government programs ranging from the evaluation of the inputs, processes, outputs, outcomes. Based on the regulation of Surabaya Mayor's Number 42 in 2011 about the details of basic tasks and functions of the Labour Department city of Surabaya is a labor environment in the area of Government of the city of Surabaya. Training program requiring the Community enacted every year. But the programs that performed the Labor Department city of Surabaya is still not able to maximum and there are still some obstacles in this program. Starting from it before this training was held and when this training program was completed, need a good cooperation between the citizens of the city of Surabaya Work with the Department of force in order to Achieve the maximum. Start of program additions, improvements, and the results of the program. To Consider the citizens of Surabaya is critical in the passage of the entrepreneurial training program in order to Achieve maximum success and in accordance with the expectations of the Government of the city of Surabaya. Keywords: Program, training, entrepreneurship. Abstrak Evaluasi Program Pelatihan Kewirausahaan Untuk Menciptakan Lapangan Kerja. Usaha yang dilakukan pemerintah mengurangi jumlah orang yang belum bekerja di kota Surabaya adalah dengan melakukan pelatihan kewirausahaan kepada orang-orang agar mereka bisa mendapatkan pekerjaan. apabila tidak dilakukan usaha itu jumlah pengangguran banyak sekali. Sebuah program ini yang diaktifkan olehÂ  pemerintah agar bisa diharapkan membuka kesempatan bekerja bagi masyarakat. Sasaran dari program pelatihan kewirausahaan ini masyarakat surabaya. Program ini dibantu lembaga terpercaya agar bisa mencapai keberhasilan. Dengan itu kita akan mengetahui program dari pemerintah mulai dari evaluasi input, proses, output, outcome. Berdasarkan peraturan walikota Surabaya Nomor 42 Tahun 2011 tentang rincian tugas pokok dan fungsi Dinas Tenaga Kerja Kota Surabaya adalah pembantuan di bidang tenaga kerja di wilayah lingkungan pemerintah Kota Surabaya. Program pelatihan yang mengikut sertakan masyarakat diberlakukan setiap tahun. Namun program yang dilakukan Dinas Tenaga Kerja Kota Surabaya masih belum bisa maksimal dan masih terdapat beberapa kendala dalam program ini. Mulai dari hal sebelum pelatihan ini berlangsung dan saat program pelatihan ini selesai dilakukan, perlu kerja sama yang baik antara warga kota Surabaya dengan Dinas Tenaga Kerja Kota Surabaya agar bisa mencapai hal yang maksimal. Mulai dari penambahan program, perbaikan, dan hasil dari program. Perlu dipertimbangkan warga Surabaya sangat penting dalam berjalannya program pelatihan kewirausahaan agar bisa mencapai keberhasilan yang maksimal dan sesuai dengan harapan pemerintah kota Surabaya. Kata kunci: Program, pelatihan, kewirausahaan